A microprocessor based PWM waveform generators; Digital motor speed controller; Building a network adapter card for IBM PC working in a ring topology local area network part 1; Graphical facilities for power system representation; Development of frame processor card; Design of data communication modem (Phase 1); Point on wave switch; Computer failure diagnostic systems : version 2.0; Parameter estimation of electrical machine 68000 based controller; Digital simulation of synchronous machine; General fault analysis / [mikrofilem] - Gerard Christopher Agnelo; Harjeet Singh Inderjeet Singh; Idawati Hamdan; Kalai Selvan Subramaniam; Mohd. Razaki Daud; Rosli Hasim Mohd. Nadzri; Sagar Ramoo; Sathia Selan Diraviyam; Stephen AK Sapat; Theng, Kin Woon; Chong, Aik Kean (1991)
PSZKLL